2020
DOI: 10.2147/tcrm.s272771
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dislocation Height Performs Well in Predicting the Use of Subtrochanteric Osteotomy in Crowe Type IV Hips</p>

Abstract: The purpose of this study was to determine whether dislocation height can predict the use of subtrochanteric osteotomy in patients with Crowe type IV hip dysplasia. Patients and Methods: We retrospectively included 102 patients affected by unilateral Crowe type IV developmental dysplasia who underwent primary total hip arthroplasty with modular cementless stem from April 2008 to May 2019 in our institution. Based on radiographs and operative notes, we found 62 hip arthroplasties were performed with subtrochant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…We also analyzed the influence of the intertrochanteric distance on STO and found it had poor predictive value. Sun et al 15 . revealed that indicator of dislocation height was useful in predicting the use of STO during THA for Crowe unilateral Crowe IV DDH.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also analyzed the influence of the intertrochanteric distance on STO and found it had poor predictive value. Sun et al 15 . revealed that indicator of dislocation height was useful in predicting the use of STO during THA for Crowe unilateral Crowe IV DDH.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure had been described in detail in our previous studies 3,15,16 . A posterolateral approach was used in all patients.…”
Section: Approach and Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…The detailed surgical procedure was almost the same as previously described in the literatures. 13 , 14 All acetabular cups were implanted at the anatomical position. No bone grafts were used to increase the cup coverage.…”
Section: Methodsmentioning
confidence: 99%